Food security stocks and the WTO legal framework - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2017)
The international trading system’s ability to operate adequately is important for global economic development, poverty alleviation, and food security. Of particular importance to the global trading system is the set of multilateral trade rules first defined under the General Agreement on Trade and Tariffs (GATT) in 1948 and later expanded during the different rounds of trade negotiations and the agreements reached in the Uruguay Round in 1995, which established the World Trade Organization (WTO). This round, however, left unresolved several critical issues regarding appropriate rules for global agriculture and other topics of importance for developing countries, and WTO members have been trying to settle these remaining questions ever since. The Doha Round, launched in 2001 during the fourth WTO Ministerial Conference, focused specifically on the development agenda.